Tramaturgy of Knowledge: an expanded methodology in the Performing Arts (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Structured on principles of memory, narrative, creative process and writing, this article presents the methodology called “tramaturgia de sabenças”, an extension of the concept “corpo griot” (Fernandes, 2022), in which the body is understood by the origin of its trajectory from contemporary movements in the Performing Arts under a countercolonial perspective. Through intersections between expanded dramaturgies and knowledge of oral tradition, the study was related to the ancestral knowledge of the “loiceiras” (clay potters) of the municipality of Remígio (PB), intertwining their stories with dance improvisation, making scenic compositions of movement and an audiovisual performance documentary flourish.
Keywords: Tramaturgy of knowledge; expanded dramaturgies; creation process; Dishware; audiovisual